2011
DOI: 10.1038/ijir.2011.36
|View full text |Cite
|
Sign up to set email alerts
|

Rat as an animal model for Peyronie's disease research: a review of current methods and the peer-reviewed literature

Abstract: While the exact mechanism of Peyronie's disease (PD) remains an enigma, the pathophysiology of PD is considered to be multifactorial, with interactions of genetic predisposition, trauma, tissue inflammation and aberrant wound healing. A non-systematic review of the existing English language literature pertaining to the use of rodent models in the evaluation of PD was performed using the Medline database. Multiple free-text searches were performed on key words: animal models of PD, transforming growth factor b1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…As suggested by Chung, the persistence of fi brin elicits an acute and, later, a chronic infl ammatory response and subsequent production of profi brotic factors (TGF-β1), and reactive oxygen species induce the development of the fi brotic plaque [ 8 ]. In 1997, Somers and coworkers, by using an experimental model on plaque tissue specimens, found that deposition of fi brin in plaque tissue is consistent with the hypothesis that repetitive microvascular injury results in fi brin deposition in the tissue space and has served to provide insights into the pathophysiology of Peyronie's disease [ 5 ].…”
Section: Fibrin Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…As suggested by Chung, the persistence of fi brin elicits an acute and, later, a chronic infl ammatory response and subsequent production of profi brotic factors (TGF-β1), and reactive oxygen species induce the development of the fi brotic plaque [ 8 ]. In 1997, Somers and coworkers, by using an experimental model on plaque tissue specimens, found that deposition of fi brin in plaque tissue is consistent with the hypothesis that repetitive microvascular injury results in fi brin deposition in the tissue space and has served to provide insights into the pathophysiology of Peyronie's disease [ 5 ].…”
Section: Fibrin Modelmentioning
confidence: 99%
“…Fibrin is an effective chemoattractant and chemotactic factor and promotes ingrowth of infl ammatory cells, macrophages, and fi broblast and induces collagen synthesis by fi broblast [ 8 ]. In 2003, Davilla et al by using a new animal model for PD found that fi brin, when introduced into the tunica albuginea of the rat penis, acts as a potential profi brotic protein, possibly via the local release of TGF-β1, and induces a plaque not only histologically similar to that induced by TGF-β1 but to that of the human condition [ 3 ].…”
Section: Fibrin Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the anticoagulation is added in, fibrin is still very easy to be freezing. Hence, using a small needle to inject fibrin is extremely difficult [26]. Some researchers induced rats spontaneously forming PD using the gene mutation technology.…”
Section: Discussionmentioning
confidence: 99%